Proceedings of the 2018 National Toxicology Program Satellite Symposium. (December 2018) - Elmore, Susan A.; Carreira, Vinicius; Labriola, Caralyn S.; Mahapatra, Debabrata; McKeag, Sean R.; Rinke, Matthias; Shackelford, Cynthia; Singh, Bhanu; Talley, Ashley; Wallace, Shannon M.; Wancket, Lyn M.; Willson, Cynthia J.
The 2018 annual National Toxicology Program Satellite Symposium, entitled "Pathology Potpourri, " was held in Indianapolis, Indiana, at the Society of Toxicologic Pathology's 37th annual meeting. The goal of this symposium was to present and discuss challenging diagnostic pathology and/or nomenclature issues. This article presents summaries of the speakers' talks along with select images that were used by the audience for voting and discussion. Various lesions and other topics covered during the symposium included seminiferous tubule dysgenesis in rats, ameloblast and odontoblast degeneration/necrosis in a Sprague Dawley rat, intestinal leiomyositis in a beagle dog, gallbladder mucinous hyperplasia, focus of hepatocellular alteration and bile duct alteration in otters, renal tubule cytoplasmic vacuolation with basophilic granules in mice treated swith antisense oligonucleotide therapy, a uterine choriocarcinoma in a rhesus macaque, and rete ovarii proliferative ovarian lesions in various aged rat strains. One particularly provocative lesion was a malignant neoplastic proliferation in the renal pelvic region of a cynomolgus macaque from a 21-day study. Additional challenging lesions included thyroid proliferative lesions in zebra fish and gross findings in fish larvae during routine chemical screening. The Rabbit and Minipig International Harmonization of Nomenclature and Diagnostic Criteria Organ Working Groups also presented a series of challenging lesions.